THE INTRODUCTION OF THE NEW ECONOMIC POLICY IN TURKESTAN AND ITS CONSEQUENCES - Акбoева Зебинисо Джалолиддиновна (TARIXIY TADQIQOTLAR, 2026)
In the 1920s, the implementation of the New Economic Policy in the Turkestan region had a significant impact on the socio-economic spheres of regional life. The study of the history of this period is currently considered one of the most relevant scholarly issues. This article analyzes the process of implementing the New Economic Policy in the Turkestan Autonomous Soviet Socialist Republic and examines its main outcomes.